Introduction to Vietnamese law (Hồng Đức, 2013)
Overview of the Vietnamese state and legal system. Human rights and ensuring business freedoms in Vietnam. The civil law. Criminal law. Vietnamese law on investment. law on business organizations. Commercial law. Labor law. Land law. Tax law. Civil relationships with foreign elemnets